The Effect of Risk Management on Aviation Logistics Effectiveness with Operational Performance as a Mediating Variable at the Cargo Terminal of Sentani Airport - Andi Batari Toja; Ukkasyah Sabbit Aqdamana Lubis; Rifqi Raza Bunahri (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study examines operational challenges in air cargo services, including delays, security risks, limited infrastructure, and uncertain weather conditions. The study aims to analyse the direct effect of risk management on operational performance and logistics effectiveness, as well as the mediating role of operational performance. A quantitative cross-sectional design was applied to all 30 employees of In Journey Aviation Services at Sentani Airport using saturated sampling. Data were collected through a five-point Likert-scale questionnaire and analysed using partial least squares structural equation modelling. The results show that risk management has a positive and significant effect on operational performance and logistics effectiveness. Operational performance also has a positive and significant effect on logistics effectiveness. In addition, operational performance partially mediates the relationship between risk management and logistics effectiveness. The findings conclude that effective risk management improves aviation logistics services both directly and through stronger operational performance, thereby supporting safer, more reliable, and more efficient cargo handling at Sentani Airport.